Effect of reimplanting with Ralgro on performance and carcass characteristics of feedlot heifers - Simms, D.; Kuhl, Gerry L.; Tonn, S.; Schalles, R. (Kansas State University. Agricultural Experiment Station, 2011)
A field study was conducted to evaluate the effect of reimplanting, and of implanting technique, on the performance of yearling heifers. Daily gains of reimplanted, single implanted and non-implanted cattle averaged 3.00, 2.93 and 2.81 lb, respectively. Implanting Ralgro at the base of the ear produced a slight and not statically significant increase in again over the “old” site 1 to 2 in. from the base of the ear. Feed efficiency of the single implant heifers was 5.5% better than controls, with an additional 1.9% improvement due to reimplanting. Carcass characteristics were not materially influenced by implant treatment.
Keywords: Beef; Reimplanting; Performance; Carcass; Heifers